Passively Q-Switched Erbium-Doped Fibre Laser Using Cobalt Oxide Nanocubes As A Saturable Absorber - Nady, Ahmad; Ahmed, Mahmoud Hazzaa M.; Numan, Arshid; T. Subramaniam, Ramesh; Abdul Latiff, Anas; Ooi, Raymond C. H.; Arof, Hamzah; Harun, Sulaiman Wadi (Taylor & Francis Group., 2017)
We demonstrate a Q-switched Erbium-doped fiber laser (EDFL) utilizing cobalt oxide (Co3O4) nanocubes film based saturable absorber (SA) as a passive Q-switcher. Co3O4 nanocubes are embedded into a polyethylene oxide film to produce a high nonlinear optical response, which is useful for SA application. It has saturation intensity and modulation depth of 3 MW/cm2 and 0.35 %, respectively. The proposed laser cavity successfully generates a stable pulse train where the pulse repetition rate is tunable from 29.8 to 70.92 kHz and the pulse-width reduces from 10.9 to 5.02 μs as the 980 nm pump power increases. This result indicates that the Co3O4 is excellent for constructing an SA that can be used in producing a passively Q-switched fiber laser operating at a low pump intensity. To the best of our knowledge, this is the first demonstration of Co3O4 film based fiber laser.